(untitled) (Journal of Nepal Physical Society, 2021)
This article deals about the experimental measurement of plasma potential, ion saturation current and Mach number obtained with the variation of power, operating gas pressure and radial position using retarding field energy analyzer. We employed a retarding field energy analyzer by rotating with different angles such as 0° (facing toward source), 90° (facing side walls) and 180° (facing opposite the source). The coil current is varied from 0 to 15 A to produce the magnetic field which is used to confine the plasma. The flow of plasma has been characterized which was found to be subsonic. The low-temperature plasma is produced by means of a 13.56 MHz helicon plasma source at 300-1000 kW radio frequency power. The plasma is expanding from 13.8 cm diameter source into a 150 cm long diffusion chamber of 60 cm diameter.